Immunogenicity and reactogenicity of a novel hexavalent DTPa-HBV-IPV/Hib vaccine compared to separate concomitant injections of DTPa-IPV/Hib and HBV vaccines, when administered according to a 3, 5 and 11 month vaccination schedule - Avdicová, Mária; Prikazský, Viktor; Hudecková, Henrieta; Schuerman, Lode; Willems, Paul (European journal of pediatrics, 2002)
In an open randomised trial, 312 eligible infants were enrolled to receive either a single injection of the hexavalent diphtheria-tetanus-acellular pertussis-hepatitis B virus-inactivated polio/ Haemophilus influenzae b (DTPa-HBV-IPV/Hib) vaccine, or concomitant injections of commercial DTPa-IPV/Hib and HBV vaccines (comparator). Vaccines were administered at 3, 5 and 11 months of age. The statistical approach for non-inferiority showed that the DTPa-HBV-IPV/Hib vaccine was at least as immunogenic as the comparator vaccines in terms of immunogenicity of all antigens 1 month after the 2nd dose. Non-inferiority criteria were also met immediately before and 1 month after the 3rd dose for all antigens except poliovirus type 3 prior to the 3rd dose. The majority of subjects were seroprotected against diphtheria, tetanus, polyribosyl-ribitol-phosphate, hepatitis B and poliovirus after the 2nd dose and maintained seroprotective antibody levels until the 3rd dose. A marked difference was observed in anti-HBs antibody geometric mean antibody concentrations (GMCs) at 1 month after the 2nd dose (higher GMCs in DTPa-HBV-IPV/Hib group). Reactogenicity (incidence of solicited local and general symptoms) was similar between the two study groups and no vaccine-related serious adverse events occurred. the new diphtheria-tetanus-acellular pertussis-hepatitis B virus-inactivated polio/ Haemophilus influenzae b vaccine administered at 3, 5 and 11 months of age was safe and at least as immunogenic as the comparator vaccines thus providing an effective and more comfortable option for this infant vaccination schedule.